2018
DOI: 10.2340/00015555-2901
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis Risk of Cutaneous Squamous Cell Carcinoma in Organ Transplant Recipients and Immunocompetent Patients

Abstract: Organ transplant recipients (OTRs) have a high incidence of cutaneous squamous cell carcinoma (cSCC), and immunosuppression has been reported to be an important risk factor for metastasis. The aim of this study was to identify the metastasis risk over a 10-year period for 593 patients with cSCC, of whom 134 were OTR and 459 were immunocompetent. Metastasis incidence rate was 1,046 (95% confidence interval (95% CI) 524-2,096) per 100,000 person years in OTR and 656 (95% CI; 388-1,107) in immunocompetent patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The median duration from the first cSCC until metastasis was the longest for OTRs, which is in line with a retrospective study among 593 cSCC patients showing a longer mean duration between cSCC diagnosis and metastasis detection in the OTR group than in immunocompetent patients because in most cases, a subsequent cSCC causes metastasis rather than the first cSCC. 28,29 On the other hand, fewer cSCCs develop in patients with hematologic malignancies than in OTRs, but their cSCCs tend to behave more aggressively, 14 which is supported by our findings that 63% of all mcSCCs in these patients resulted from first cSCCs. These findings may suggest a pivotal role for the total burden of cSCCs in the mcSCC pathogenesis among OTRs and, rather, for the individual cSCC lesion in patients with hematologic malignancies.…”
Section: Discussionsupporting
confidence: 81%
“…The median duration from the first cSCC until metastasis was the longest for OTRs, which is in line with a retrospective study among 593 cSCC patients showing a longer mean duration between cSCC diagnosis and metastasis detection in the OTR group than in immunocompetent patients because in most cases, a subsequent cSCC causes metastasis rather than the first cSCC. 28,29 On the other hand, fewer cSCCs develop in patients with hematologic malignancies than in OTRs, but their cSCCs tend to behave more aggressively, 14 which is supported by our findings that 63% of all mcSCCs in these patients resulted from first cSCCs. These findings may suggest a pivotal role for the total burden of cSCCs in the mcSCC pathogenesis among OTRs and, rather, for the individual cSCC lesion in patients with hematologic malignancies.…”
Section: Discussionsupporting
confidence: 81%
“…Only a few studies reported on immunosuppressed patients in their cohort. Patients on immunosuppression develop cSCC that tend to behave more aggressively, with a higher rate of both local recurrence and metastasis compared to immunocompetent patients (9,(33)(34)(35). Also, peripheral tumor borders can be difficult to properly define because of severe damage to the surrounding skin.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of high‐risk tumours obviously influences the metastasis rate in a cohort. Another important factor to take into account is age, as older age is a risk factor for metastasis . In the OTR, the age of cSCC patients is lower compared to the immunocompetent population and therefore could contribute to the lower metastasis risk per cSCC in these group.…”
Section: Discussionmentioning
confidence: 99%